1986
DOI: 10.1128/aac.30.6.835
|View full text |Cite
|
Sign up to set email alerts
|

Penicillins, cephalosporins, and tetracyclines in treatment of hamsters with fatal leptospirosis

Abstract: A predictable 6- to 7-day course of a fatal Leptospira interrogans serovar bataviae infection in experimentally infected mature 110- to 150-g hamsters was used to evaluate the therapeutic efficacy of conventionally used and newer antibiotics. Active drugs were ampicillin, bacampicillin, cyclacillin, piperacillin, mezlocillin, doxycycline, chlortetracycline, cefotaxime, and moxalactam. Cephalexin, cefadroxil, cefamandole, and cefoperazone showed little or no activity in preliminary studies. In delayed treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 10 publications
1
22
0
Order By: Relevance
“…The observed efficacy of doxycycline was consistent with that reported in previous leptospiral animal research (1,8). The efficacy of the two macrolide antimicrobial agents azithromycin and clarithromycin supports earlier research that demonstrated in vivo efficacy of erythromycin in treating various rodent models of leptospirosis (2, 5, 9).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The observed efficacy of doxycycline was consistent with that reported in previous leptospiral animal research (1,8). The efficacy of the two macrolide antimicrobial agents azithromycin and clarithromycin supports earlier research that demonstrated in vivo efficacy of erythromycin in treating various rodent models of leptospirosis (2, 5, 9).…”
Section: Discussionsupporting
confidence: 81%
“…Antimicrobial therapy in all experiments was begun on day 2 (infection was on day 0) and continued for 5 days. Six concentrations of azithromycin (6.25, 12.5, 25, 50, 100, and 200 mg/kg), eight concentrations of clarithromycin (1,5,10,15,20,40,60, and 100 mg/kg), and six concentrations of telithromycin (1,5,10,15,20, and 40 mg/kg) were tested. The efficacy of various doxycycline concentrations (1,5,10,15,50, and 100 mg/kg) was also examined in the model for further comparison.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the previous studies with experimental animals (2,20), we tried to define experimental conditions as close as possible to those in a natural infection: (i) the infecting serovar…”
Section: Discussionmentioning
confidence: 99%
“…10 However, when this work was repeated 20 years later by Alexander and Rule, 11 first generation cephalosporins (cefadroxil and cephalexin), even in high doses, were not shown to be effective against leptospirosis in their hamster model. Their work did show a survival benefit for second (cefamandole) and third (cefoperazone, cefotaxime, and moxalactam) generation cephalosporins.…”
Section: Introductionmentioning
confidence: 99%